2017
DOI: 10.1159/000479991
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-Like Factor 2 Regulates Degradation of Type II Collagen by Suppressing the Expression of Matrix Metalloproteinase (MMP)-13

Abstract: Background/Aims: Krüppel-like factor 2 (KLF2) plays an essential role in the inhibition of endothelial cell and macrophage activation during the inflammatory process. However, the roles of KLF2 in chondrocytes and the pathological progression of osteoarthritis (OA) remain unknown. The aim of this study was to investigate the function of KLF2 in the inhibition of cartilage matrix destruction in chondrocytes. Methods: RT-PCR and western blot analysis was used to determine the expression of KLF2 in human chondroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
1
15
1
Order By: Relevance
“…Considering these facts, KLF2 can be a potential regulator of expression of MMP s in chondrocytes, and related to OA onset and/or progression. KLF2 expression was reportedly downregulated in human OA chondrocytes contrary to our results, wherein KLF2 upregulation suppressed MMP13 expression and ameliorated type II collagen degradation [ 38 ]. Although no information was provided on OA staging in Yuan’s report, this discrepancy could be a result of the difference in OA grade, as expression patterns of specific genes in chondrocytes depend on the stage of OA [ 39 ].…”
Section: Discussioncontrasting
confidence: 94%
“…Considering these facts, KLF2 can be a potential regulator of expression of MMP s in chondrocytes, and related to OA onset and/or progression. KLF2 expression was reportedly downregulated in human OA chondrocytes contrary to our results, wherein KLF2 upregulation suppressed MMP13 expression and ameliorated type II collagen degradation [ 38 ]. Although no information was provided on OA staging in Yuan’s report, this discrepancy could be a result of the difference in OA grade, as expression patterns of specific genes in chondrocytes depend on the stage of OA [ 39 ].…”
Section: Discussioncontrasting
confidence: 94%
“…It has been reported that KLF2 regulates cellular growth and differentiation [35]. KLF2 was involved in degradation of type II collagen, a primary component of the extracellular matrix in articular cartilage, through inhibiting matrix metalloproteinase-13 expression [36]. Interestingly, KLF2 was reported to be significantly increased during the osteoblastic differentiation process and KLF2 could promote the expression of the osteoblastic differentiation marker genes Alp, Osx, and Ocn and stimulate mineralization by enhancing the expression of and interacting with Runx2 [37].…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) family function in irreversible matrix degradation and subsequent joint destruction in OA . Previous reports showed that Interleukin‐1β (IL‐1β) and tumour necrosis factor‐α (TNF‐α) are two most potent catabolic factors that increase the production of inflammatory mediators and the expression of MMPs in chondrocytes .…”
Section: Introductionmentioning
confidence: 99%
“…12 Matrix metalloproteinases (MMPs) family function in irreversible matrix degradation and subsequent joint destruction in OA. 13 Previous reports showed that Interleukin-1β (IL-1β) and tumour necrosis factor-α (TNF-α) are two most potent catabolic factors that increase the production of inflammatory mediators and the expression of MMPs in chondrocytes. 14 Among these MMPs, MMP-13 has caught a lot of attention in that it was significantly overexpressed in both joints and articular cartilage in OA patients and could hardly be detected in normal tissues.…”
Section: Introductionmentioning
confidence: 99%